STUDY OF THE FATTY ACIDS’ COMPOSITION OF INFLORESCENCES OF TAGETES ERECTA L. VAR. «ALASKA - Малюгина, Елена; Смойловская, Галина; Мазулин, Александр (SWorldJournal, 2020)
Marigolds (Tagetes erecta L.) is one of the most common and widely cultivated species of the genus Tagetes L. of family Asteraceae. Plants of the genus Tagetes L. are known for a wide range of biological activity and the content of various classes of biol